2014
DOI: 10.1002/lt.23879
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in liver transplantation-Limited application of the liver donor risk index

Abstract: Introduction The liver donor risk index (LDRI), originally developed in 2006 by Feng et. al and since modified, is a method of evaluating liver grafts from deceased donors by determining the relative risk of graft failure post transplantation. Methods Online and paper surveys sent to liver transplant physicians asking about their attitudes and practices regarding decision-making in liver transplantation and the role of LDRI. Results 147 of 401 (37%) eligible respondents returned partial or complete surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Introducing a change in clinical practice has been long known to be challenging for various reasons including physician resistance or incomplete understanding (17,18), and KDPI might not have been an exception. This explanation is also supported by a survey (19) on liver transplant surgeons’ attitudes toward the Liver Donor Risk Index (LDRI), which is analogous to KDRI for liver donors: 73% of liver transplant surgeons surveyed believed that LDRI does not adequately describe donor-associated risk and 83% rarely or never discussed LDRI with their patients. Additionally, given the association between KDPI and discard, the factors constituting KDPI could have already been affecting discard practice, and KDPI may have not provided much additional information.…”
Section: Discussionmentioning
confidence: 94%
“…Introducing a change in clinical practice has been long known to be challenging for various reasons including physician resistance or incomplete understanding (17,18), and KDPI might not have been an exception. This explanation is also supported by a survey (19) on liver transplant surgeons’ attitudes toward the Liver Donor Risk Index (LDRI), which is analogous to KDRI for liver donors: 73% of liver transplant surgeons surveyed believed that LDRI does not adequately describe donor-associated risk and 83% rarely or never discussed LDRI with their patients. Additionally, given the association between KDPI and discard, the factors constituting KDPI could have already been affecting discard practice, and KDPI may have not provided much additional information.…”
Section: Discussionmentioning
confidence: 94%
“…Donor‐derived risk scores, however, showed weak correlations when tested in different populations and might not be able to correctly predict graft survival . A recent analysis showed that, while numerous risk indices have been published, they are not frequently used in daily practice .…”
mentioning
confidence: 99%
“…We think that this new DRM is more complete than previous models because it contains all relevant factors that have (significant) impact on outcome after LT. Although a recent study described the limited use of the DRI in the Organ Procurement and Transplantation Network (OPTN), the most important issues named are addressed by the new DRM model . Next to the creation of the DRM, the ET‐DRI was validated in this new cohort, confirming its correlation with outcome after LT in the Eurotransplant region.…”
Section: Discussionmentioning
confidence: 75%